FORMULATION DOSAGE FORM OF TABLET CONTAINING KEPEL LEAF EXTRACT (Stelechocarpus burahol (Blume) Hook.f & Thomson) AS AN ANTIMICROBIAL AGENTS - Hilda Maysarah; Meutia Faradilla; Tedy Kurniawan Bakri; Misrahanum Misrahanum (Jurnal Natural, 2019)
Pharmaceutical dosage form that contains herbal materials has been developed in order to make it easy to consume. Tablet is one of pharmaceutical dosage form that generally used. A formulation and antimicrobial test of tablet containing extract of Kepel leaf with different concentration of diluents, binders, and disintegrants has been studied. The evaluation test showed that formulation consist of  25 % of Kepel leaf extract, 64.5 % of avicel PH 102, 2 % of PVP, 7 % of amprotab, 0.5 % of aerosil, and 1 % of talcum are better than the others. The experimental method used in this study was wet granulation. From the result of the mass granulation evaluation, it was obtain that speed flow without vibration was 2.53 second, with vibration was 2.83 second, bulk density was 0.329 g/mL, taped density was 0.376 g/mL and compressibility was 12.65 %. The result of tablet evaluation obtained that the average weight was 498 mg, with the average hardness was 4 kg/cm2 and disintegration time was 2.36 minutes. Antimicrobial test showed that in the concentration of 50 mg/mL, had average inhibitory diameter against S. aureus of 12.96 mm, P. aeruginosa 12.7 mm, and against B. subtilis was 12.53 mm. Whereas, concentration of 62.5 mg/mL had average inhibitory diameter against S. aureus was 13.5 mm, P. aeruginosa was 13.56 mm, and against B. subtilis was 13.43 mm. Both concentrations did not have antimicrobial activity against E.coli.